2016
DOI: 10.1136/bmj.i4482
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation and risks of cardiovascular disease, renal disease, and death: systematic review and meta-analysis

Abstract: ObjeCtiveTo quantify the association between atrial fibrillation and cardiovascular disease, renal disease, and death.Design Systematic review and meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
436
0
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 627 publications
(472 citation statements)
references
References 126 publications
20
436
0
16
Order By: Relevance
“…Odutayo et al 20. reported that the risk of ischemic stroke was 2.33 times than that in people without atrial fibrillation in their cohort study.…”
Section: Discussionmentioning
confidence: 92%
“…Odutayo et al 20. reported that the risk of ischemic stroke was 2.33 times than that in people without atrial fibrillation in their cohort study.…”
Section: Discussionmentioning
confidence: 92%
“…Studies that accounted for the largest share of heterogeneity were sequentially and cumulatively excluded until I 2 was <50%. We then examined whether the OR estimates were consistent [36]. Evidence of publication bias was examined using funnel plots.…”
Section: Resultsmentioning
confidence: 99%
“…and S.G.) independently used the Newcastle-Ottawa quality assessment scale for case-control studies to assess the risk of bias [31][32][33][34][35]. Subsequently, the studies were considered at a low risk of bias if they achieved a full rating in at least two categories of selection, comparability, or outcome assessment [36].…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
“…(8) A large meta-analysis involving over half a million patients with AF over a median follow-up period ranging from 3 -6 years, highlights that this arrhythmia is associated with increased absolute risk of heart failure (11.1 events/1 000 person-years), chronic kidney disease (6.6/1 000), stroke (3.6/1 000) and ischaemic heart disease (1.4/1 000) as well as excess cardiovascular (2.6/1 000) and all-cause mortality (3.8/1 000). (9) Certainly this association does not imply direct causality but it does question why a correlation with excess mortality and morbidity from both cardiovascular and non-cardiovascular causes exists.…”
Section: Atrial Fibrillation As a Vascular Diseasementioning
confidence: 99%